2005
DOI: 10.1029/2005rs003264
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cluster's electric antennas in space: Application to plasma diagnostics

Abstract: [1] The main characteristics of the long-boom electric antennas installed on board the Cluster satellites are derived from finite element modeling in a kinetic and isotropic space plasma, in the frequency range of about 1-100 kHz. The model is based on the surface charge distribution method in quasi-static conditions. The impedances of both types of antenna, i.e., the double-wire and the double-probe, are computed versus the frequency normalized with respect to the local plasma frequency and for several differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Recently, modeling and mutual impedance tests of the Cluster antennas have indicated that under certain conditions, the effective length of the antennas may be shorter than their actual physical length [ Béghin et al , 2005]. The results of these tests indicate that we may still be underestimating the actual waveform amplitudes, even when we correct for spin modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, modeling and mutual impedance tests of the Cluster antennas have indicated that under certain conditions, the effective length of the antennas may be shorter than their actual physical length [ Béghin et al , 2005]. The results of these tests indicate that we may still be underestimating the actual waveform amplitudes, even when we correct for spin modulation.…”
Section: Discussionmentioning
confidence: 99%
“…1b and c display the spectral power density of electric field integrated along the effective length of the antenna, a quantity expressed in units of V 2 rms Hz −1 . The latter quantity, closer to the raw measurement, is directly proportional to the former, according to a coefficient identical on both spacecraft, since their respective receiving antenna have the same physical length and provided that the plasma regime is similar enough on each platform for effective lengths to be equal to each other (Béghin et al, 2005).…”
Section: Measured Quantitiesmentioning
confidence: 99%
“…As examined in many past works (e.g., [28]), it is shown that the resistance, the real part of the impedance, has a peak value, and the reactance, the imaginary part, shows a drastic change both at the plasma frequency. The impedance modification by ES waves depends on the Debye length and its relative ratio to the antenna length, which is discussed in the latest work with the CLUSTER antenna modeling [38]. In the current simulation, the Debye length of the background plasma is 4.5 m, while the entire length of the antenna is 24 m. In this situation, the signature of the resonance around the plasma frequency of the background plasma is rather difficult to be observed because it is generally known that it appears for antenna lengths around 8-10 m Debye lengths.…”
Section: ) Plasma Environment With Photoelectron Emissionmentioning
confidence: 99%
“…In this method, the ion sheath interface is given as a parameter. The antenna analysis with the SCD method has been successfully applied to the interpretation of impedance measurements onboard spacecraft such as the CLUSTER satellite [38].…”
Section: A Introductionmentioning
confidence: 99%